2005
DOI: 10.1016/j.bbamem.2005.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Two-color fluorescent probes for imaging the dipole potential of cell plasma membranes

Abstract: The dipole potential (Psi(d)) constitutes a large and functionally important part of the electrostatic potential of cell plasma membranes. However, its direct measurement is not possible. Herein, new 3-hydroxyflavone fluorescent probes were developed that respond strongly to Psi(d) changes by a variation of the intensity ratio of their two well-separated fluorescence bands. Using fluorescence spectroscopy with cell suspensions and confocal microscopy with adherent cells, we showed, for the first time, two-colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…They were suggested for probing biomembrane structures by locating the dyes at different orientations and depths (Klymchenko et al 2002a). More sophisticated functional dyes sense variations of dipole potential in membranes of living cells (Shynkar et al 2005) and are able to detect the early steps of apoptosis (Shynkar et al 2007). Derivatives of these dyes for covalent labeling of amino and SH-groups were also obtained , which can be used in various types of protein and peptide biosensors.…”
Section: Supersensitive Multicolor Ratiometric Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were suggested for probing biomembrane structures by locating the dyes at different orientations and depths (Klymchenko et al 2002a). More sophisticated functional dyes sense variations of dipole potential in membranes of living cells (Shynkar et al 2005) and are able to detect the early steps of apoptosis (Shynkar et al 2007). Derivatives of these dyes for covalent labeling of amino and SH-groups were also obtained , which can be used in various types of protein and peptide biosensors.…”
Section: Supersensitive Multicolor Ratiometric Dyesmentioning
confidence: 99%
“…Moreover, a multiparametric analysis based on band deconvolution showed that these changes are independent from the hydration parameter (M' Baye et al 2006). In order to avoid their fast internalization and/or poor staining of plasma membranes of the living cells, a second generation of probes were introduced (Shynkar et al 2005).…”
Section: Supersensitive Multicolor Ratiometric Dyesmentioning
confidence: 99%
“…3 ) that are analogs of the previous pair, bearing zwitterionic groups and long hydrophobic tails at the opposite sides of the fl uorophore. This second generation of probes demonstrates a fair selectivity for cell plasma membranes and exhibits strong ratiometric variations of their two emission bands versus Ψ D in living cells [ 104 ].…”
Section: Electrostatic Membrane Potentialsmentioning
confidence: 99%
“…It was shown that even the simplest representatives of the 3HF family, 4 0 -dialkylamino-3-hydroxyflavones, can provide a strong ratiometric response to the presence of water in reverse micelles (Klymchenko and Demchenko, 2002b) and also to structural rearrangements (Bondar et al, 1998), surface charge/ hydration (Duportail et al, 2001(Duportail et al, , 2002 and properties of location sites (Klymchenko et al, 2004b) in phospholipid membrane vesicles. More sophisticated functional dyes sense variations of dipole potential in membranes of living cells (Shynkar et al, 2005). Derivatives of these dyes for covalent labeling of amino and SH-groups were also obtained (Klymchenko et al, 2004a), which can be used in various types of protein and peptide biosensors.…”
Section: Optimized Dyes For Two-band Wavelength-ratiometric Measuremementioning
confidence: 99%